Caesarean Scar Pregnancy: A Case Series - Chowdhury, Liza; Anjana, -; Jahan, Ishrat (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Caesarean section rate is increasing day by day. Incidence of caesarean scar pregnancy (CSP) is also increasing. Prompt and multidisciplinary approach towards diagnosis of the condition is required to reduce associated morbidity. Major haemorrhage and hysterectomy are the main risks associated with CSP. Therefore, adequate counseling and availability of surgical expertise and blood transfusion should be part of a comprehensive management strategy. There are many single reports in literature but only few case series. In this paper, 10 cases of caesarean scar pregnancy treated in Obstetrics and Gynaecology department of CMH Dhaka, CMH Jashore and Hightech Multicare Hospital Private Limited over 10 years are analyzed. Three of 10 patients had mild pain in their lower abdomen and vaginal bleeding. Seven of them had profuse bleeding during D&C for miscarriage as they were not diagnosed at the time of admission. All patients had 1 or 2 caesarean sections. Gestational age of the pregnancy was estimated from 8 to 12 weeks by the last menstrual period. 9 patients were treated surgically. Eight of them had local resection of ectopic pregnancy mass with conservation of the uterus. One patient was treated with D&C followed by intrauterine balloon catheter insertion to control excessive bleeding. There was no total or subtotal hysterectomy. One patient was treated with Inj. Methotrexate. Common symptoms of caesarean scar pregnancy are pain in the lower abdomen and variable degree of vaginal bleeding. The treatment depends on severity of symptoms, gestational age and experience of the obstetrician dealing these cases. J Bangladesh Coll Phys Surg 2019; 37(4): 191-195